Endovascular Embolization of Life Threatening Intracranial Arterio-venous Malformation - Khan, SU; Rahman, KM; Siddiqui, MR; Hoque, MA; Mondol, BA; Hussain, S; Mohammad, QD (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):438-41 The abstract of this article is available on the PubMed website